Hadith #1021 - Sahih Muslim - Abu Juhaifa (Sahih Muslim)
I came to the Messenger of Allah (ﷺ) in Mecca and he was (at that time) at al- Abtah in a red leather tent. And Bilal stepped out with ablution water for him. (And what was left out of that water) some of them got it (whereas others could not get it) and (those who got it) rubbed themselves with it. Then the Messenger of Allah (ﷺ) stepped out with a red mantle on him and I was catching a glimpse of the whiteness of his shanks. The narrator said: He (the Holy Prophet) performed the ablution.
Grade: Sahih

Hadith #1022 - Sahih Muslim - Abu Juhaifa (Sahih Muslim)
I saw the Messenger of Allah (ﷺ) (in Mecca at al-Abtah) in a red leather tent. and I saw Bilal take the ablution water (left by Allah’s Messenger), and I saw the people racing, with one another to get that ablution water. If anyone got some of it, he rubbed himself with it, and anyone who did not get any got some of the moisture from his companion’s hand. I then saw Bilal take a staff and fix it in the ground, after which the Messenger of Allah (ﷺ) came out quickly in a red mantle and le
Grade: Sahih

Hadith #1024 - Sahih Muslim - Abu Juhaifa (Sahih Muslim)
The Messenger of Allah (ﷺ) went at noon towards al-Batha’, he performed ablution, and said two rak’ahs of the Zuhr prayer and two of the ‘Asr prayer, and there was a spear in front of him. Shu’ba said and Aun made this addition to it on the authority of his father Abu Juhaifa: And the woman and the donkey passed behind it.
Grade: Sahih

Hadith #5924 - Sahih Muslim - Abu Juhaifa (Sahih Muslim)
I saw Allah’s Messenger (ﷺ) having some whiteness (in hair) at this place, and Zuhair placed one of his fingers at his chin. Juhaifa was asked how old he had been at that time. He said: I made arrows and put feathers to them (i. e. I had passed my childhood).
Grade: Sahih

Hadith #5925 - Sahih Muslim - Abu Juhaifa (Sahih Muslim)
I saw Allah’s Messenger (ﷺ) that he had white complexion and had some white hair, and Hasan b. ‘Ali resembled him.
Grade: Sahih